현대공예의 구상적 표현을 통한 내러티브 유형 연구 - 한상덕; Han Sang Deok; 강연미; Kang Yeon Mi (기초조형학연구, 2019)
본 연구의 목적은 현대공예에 나타난 구상적 표현을 통한 내러티브의 유형을 분류하고 이를 통해 관련 작가들의 작품을 분석하여 표현매체로서 현대공예의 독창적인 발전 가능성을 모색하는 것이다. 연구 방법으로는 구상적 표현방식을 통해서 이야기를 전개하는 현대공예 작품의 주제 및 제작 과정의 특징을 공예의 시각에서 분석 하였으며, 연구 대상은 현재 활동하는 미국과 유럽의 현대공예 작가로 한정하였다. 20세기 중엽 포스트모더니즘의 확산으로 인해 공동체적 이데올로기가 파괴되고 개인의 감정과 내면을 중시하는 문화가 형성되었다. 이러한 시류에 영향을 받은 현대공예는 개인의 감정을 드러내는 표현매체로 발전하였다. 표현 매체는 추상과 구상 표현으로 크게 나뉘는데 이 중 구상적 표현은 실제 대상을 연상시키는 시각 기호를 통해서 은유적인 이야기를 전달하는 것을 의미한다. 이때 시각 기호의 내러티브는 작가의 의도에 의해 여러 형식을 보이는데 이는 알레고리, 풍자, 우화의 세 가지의 유형으로 나뉘며 이를 바탕으로 6인의 현대공예 작품을 해석하여 표현매체로서 현대공예의 특징과 성격을 구체적으로 살펴 볼 수 있다. 알레고리에는 일상의 고통을 장신구로 표현한 스미스와 일용 기물의 메타포를 다루는 밈리취-그레이, 풍자에는 비즈공예 기법을 활용하여 사회적 문제를 고발하는 스콧과 현대인의 삶을 유머러스하게 표현한 메트캐프, 우화에는 뜨개질 옷을 입힌 의인화된 동물의 판 데어 레스트와 인간의 이면을 표현한 시각 이미지를 입체위에 덧씌워 초현실적인 캐릭터를 창조하는 이수포프를 대표적인 현대공예 작가로 들 수 있다. 이들은 표현 의도와 형식에는 차이를 보이지만 재료에 중심을 두며 정교한 손기술을 바탕으로 하는 공예의 속성을 통해 독특한 조형성과 정서적인 유대를 구현하였다는 공통적인 특징을 보인다. 이러한 분석은 현대공예에서의 구상적 표현은 조형적 가치뿐만 아니라 크기나 형식의 고유한 보편성에 의해 감정의 내밀한 소통이 가능한 독창적인 매체라는 결론을 나타낸다. The purpose of this study is to classify the forms of figurative expression in contemporary craft into three types. By analyzing the works of contemporary craft artist in accordance with each category, it is to explore the possibility of original development of craft as an expression medium. As a research method, the features of theme and the process of the contemporary crafts which develop the story through the figurative expressive methods, were analyzed from the craft's viewpoint. The subjects of the study were limited to the American and Europe contemporary craft artists. In the mid of 20th century, the spread of postmodernism destroyed the communal ideology and create a culture that emphasized personal feelings. Contemporary craft is influenced by these trends developed into expression media of visualizing personal emotions. The expression is divided into abstraction and figurative expression. Among them, this study analyzed the general definition and the way of how artists convey the story in order to study the aspect of development of the figurative expression. Figurative expression means conveying a metaphorical story through a visual symbol reminiscent of an actual object. While the symbol system of visual symbol has various forms according to the artist’s intention, this study is classified into the following categories: allegory, satire, and fable. In Chapter 3, based on the contents of Chapters 1 and 2, I analyzed 6 contemporary craft artists and examined the specific features of craft as an expression medium. This study analyzed the metaphor and symbols of ordinary sort of day, the conditions of satire, which are allegories according to the type of story to be conveyed, and the aspect of personified expression of characters that is the core of fable. As a result, contemporary craft based on natural materials and sophisticated hand techniques have the attributes of aesthetic value and emotional ties. Therefore, the figurative expression in contemporary craft is not only the formative value, it is concluded that it is an original medium capable of intimate communication of emotions by universality.